Financial reform and banking crises - Choudhry Tanveer Shehzad (Center for Economic Studies and ifo Institute (CESifo), 2009)
We examine the impact of various dimensions of financial reform on the likelihood of systemic and non-systemic banking crises. Using new financial reform measures for a large sample of developing and developed countries for the period 1973 to 2002, our multivariate probit modeling results suggest that conditional on adequate banking supervision, certain dimensions of financial reform reduce the likelihood of systemic crises. We also show that after a country has reformed, the introduction of further reforms becomes easier and leads to more stable financial systems. We also find some evidence that the likelihood of non-systemic crisis increases after financial reform.
Keywords: E44; G21; G28; F36; 330; banking crises; financial reform; financial fragility; Finanzsektor; Reform; Deregulierung; Bankenkrise; Finanzmarktkrise; Welt